Manajemen Risiko di SMK Muhammadiyah 1 Wates - Imam Mars Miasya Ibnu Ivan; Sendi Nurtanti; Farid Setiawan (PT. ALHAFI BERKAH INDONESIA, 2023)
Risk is a possibility or uncertainty in an activity regarding conditions that will occur later. Risks can be in the form of obstacles or opportunities, therefore every activity in an institution must have careful planning, especially in school educational institutions. Careful planning will minimize or avoid risks, so that later the quality of education can be improved. This article discusses efforts to improve the quality of education through the educational risk management process. The results of the research in this article are that risk management in an educational institution really needs to be done in order to achieve good quality education. This research uses Muhammadiyah 1 Wates Vocational School as the research sample. This research approach uses qualitative methods by processing data obtained through observations, interviews, observation and documentation which is then described through narrative text. Risk management at Muhammadiyah 1 Wates Vocational School includes several steps including 1) risk identification 2) measuring the magnitude of risk 3) risk management 4) risk evaluation 5) developing educational quality. Developing the quality of education includes handling, both handling of educators, students and also the educational curriculum.